Study the protective effect of Matricaria chamomilla flower extract against the toxicity of Entamoeba histolytica induces liver and renal dysfunctions in adult albino male rats - Ali, Abeer A.; Alattar, Shahad Abbas (Iraqi Journal of Science, 2018)
The present study was designed to show the potential role of Matricaria chamomilla flower extract against toxicity of Entamoeba histolytica . The study used 20 adult albino male rats that divide randomly to four groups (each group consist 5 rats); control group received ad libidium, group of rats administrated with 1X103 cyct/ml suspension for seven days, group of rats administrated with 1X103 cyct/ml suspension and treated with 50mg/kg extract for month, group of rats administrated with 1X103 cyct/ml suspension and treated with 100mg/kg extract for month. The results show high significant increased (P < 0.05) in levels of Alanine Aminotransferase (ALT), Aspartate Aminotransferase (AST), Alkaline Phosphatase (ALP), urea, creatinine and uric acid in rats administrated with 1X103 cyct/ml suspension. Oxidative stress factor in this group show significant increased (P < 0.05) in levels of MDA (malonedialdehyied) and significant decreased (P < 0.05) in levels of glutathione (GSH) and catalase compared with control group. While, after used M. chamomilla flower extract with Entamoeba histolytica , the results showed non significant changes (P < 0.05) in liver and kidneys function parameters. Also, MDA, GSH and catalase showed non significant changes (P < 0.05) compared with control group. It was concluded that flower extract has been potential role against toxicity of Entamoeba histolytica in adult male albino rats.